Affirmation and Negation: Reading Avicenna’s Al-‘Ibara Alongside Hellenistic Commentators - E. Burak Şaman (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The relation of priority and posteriority between the affirmation and negation, which Aristotle put forth in Peri Hermêneias, has had some important consequences in terms of logical attribution and judgement. The problem encountered here is the question of whether affirmation (i.e., affirming something of something) and negation (i.e., denying something of something) share the same status as a statement (qawl). In the fifth chapter of the first article (I.5) of al-‘Ibāra, the volume from al-Shifā corpus that corresponds to Peri Hermêneias, Avicenna deals with affirmation and negation in terms of these logical consequences and reveals his own position on the subject by way of distinguishing between attribution and judgement. However, the text of al-Shaikh al-Raīs presents some obscurities for the reader. The reason behind this obscurity is that a debate taking place among Hellenistic commentators lies in the background of Avicenna’s text. This article proposes to study this text alongside the Hellenistic commentators in order to better understand the logical problem in the relevant passages from al-‘Ibāra. Our guide in this reading will be Boethius, who wrote a Latin commentary on Peri Hermêneias. In the present study, I will try to reveal how the positions of the Hellenistic commentators (i.e., Alexander of Aphrodisias, Porphyry, and Syrianus), whose views Boethius conveyed, coincide with the views Avicenna defended and criticized regarding affirmation and negation. In this respect, my reading in this article aims to better understand Avicenna’s relevant text and its logical extensions as well as the dimensions of his relationship with Hellenistic commentators.